2016
DOI: 10.1111/risa.12637
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Use of Dynamic Transmission Models for Measles and Rubella Risk and Policy Analysis

Abstract: The devastation caused by periodic measles outbreaks motivated efforts over more than a century to mathematically model measles disease and transmission. Following the identification of rubella, which similarly presents with fever and rash and causes congenital rubella syndrome (CRS) in infants born to women first infected with rubella early in pregnancy, modelers also began to characterize rubella disease and transmission. Despite the relatively large literature, no comprehensive review to date provides an ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 207 publications
(319 reference statements)
0
46
0
3
Order By: Relevance
“…However, the transmission rate of many childhood infections and seasonal influenza abruptly changes by the host behaviour (cycles of human aggregation from school holidays, migrations, etc). Motivated by Diedrichs et al (2014), Olinky et al (2008), Uziel and Stone (2012), Keeling and Grenfell (1997), Thompson (2016), Earn et al (2000) we assume that φ can be expressed as…”
Section: Resultsmentioning
confidence: 99%
“…However, the transmission rate of many childhood infections and seasonal influenza abruptly changes by the host behaviour (cycles of human aggregation from school holidays, migrations, etc). Motivated by Diedrichs et al (2014), Olinky et al (2008), Uziel and Stone (2012), Keeling and Grenfell (1997), Thompson (2016), Earn et al (2000) we assume that φ can be expressed as…”
Section: Resultsmentioning
confidence: 99%
“…Studies in mice and NHPs have shown that MV initially infects alveolar macrophages and DCs in the lungs, instead of epithelial cells of the upper respiratory tract [2224]. Even though this is a possible entry route, it seems unlikely that a highly contagious virus with an R 0 of 12–18 [25] and of which infection with one 50% tissue culture infectious dose (TCID 50 ) is sufficient to cause productive infection in macaques [26], exclusively depends on infection of target cells in the alveoli. Additional routes of entry into a susceptible host have been postulated, including infection of CD150 + immune cells within the epithelium of the respiratory tract [18, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing the variability in current national measles and rubella immunization programs, experience with historical immunization, population structures, and viral transmission conditions, we model each area separately and then aggregate the results to regional and global levels. The model includes 180 WHO member states and three other areas (i.e., Puerto Rico, Hong Kong, and Macao) for which we found sufficient demographic and immunization data .…”
Section: Methodsmentioning
confidence: 99%
“…When outbreaks occur, some countries conduct outbreak response immunization (ORI) (i.e., outbreak SIAs [oSIAs]) and/or other public health interventions (e.g., contact tracing and isolation). Existing models for measles and rubella consider a wide range of different assumptions about the nature of immunity, transmission, population mixing, seasonality, heterogeneity, and other factors applied to real and hypothetical populations on different geographic scales . Within the last 15 years, analysts demonstrated the importance of using dynamic disease models to appropriately characterize the economic and policy impacts of interventions on population immunity for transmissible infectious diseases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation